The Effect Of Working Capital Management On Trade Credit Provision With Corporate Financial Slack As Moderating Variabel - Rossa, Elia; Marinda, Nera; Sastrodiharjo, Istianingsih; Sinlae, Fried (International Journal of Advanced Multidisciplinary, 2024)
This research aims to test and identify the effect of working capital management on trade credit provisions with corporate financial slack as a moderating variable. This research uses a sample of food and staples retailing sub-sector firms listed on the Indonesia Stock Exchange for the 2020-2022 period. The ordinary least squares (OLS) regression approach is used in this research to test the hypothesis with the help of eviews version 13. The results of this research find that working capital management has a positive and significant effect on trade credit provisions and the corporate financial slack has a negative and significant effect on the relationship between working capital management on trade credit provisions.